Low-shrinkage soluble core mold for composite material molding and manufacturing method thereof

By using a combination of aqueous acrylic resin and specific components, the shaping temperature and shrinkage of the soluble core mold are reduced, and the problems of difficult control of the existing core mold dimensional accuracy and high cost are solved, thereby achieving efficient and low-cost core mold manufacturing forming.

CN119388637AInactive Publication Date: 2025-02-07SHENYANG AIRCRAFT CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411590110.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing soluble core molds have high shrinkage during the composite forming process, which makes it difficult to control the dimensional accuracy and high cost.

Method used

Water-based acrylic resin is used as adhesive, combined with hollow glass microbeads, kaolin, graphite powder and rigid fillers, and the component ratio is regulated to reduce the shape temperature and shrinkage rate and improve mechanical properties.

Benefits of technology

It realizes a soluble core mold with low shrinkage, controllable dimensional accuracy and low cost, and is suitable for the manufacturing and molding of fiber-reinforced resin-based composite parts.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of mold manufacturing, and particularly relates to a low-shrinkage-rate soluble core mold for composite material forming and a manufacturing method of the low-shrinkage-rate soluble core mold. The shrinkage rate range of the core mold material after curing and shaping is 0.2%-0.6%. The soluble core mold manufactured through the method is light in weight, the density ranges from 1.03 g / cm < 3 > to 1.05 g / cm < 3 >, and the soluble core mold is only slightly heavier than water. The compression strength can reach 10 MPa or above, and the pressure requirement in composite material forming can be met. And during demolding, the core mold can be dissolved and collapsed by common solvents such as water, ethanol and acetone, and the use cost is low. The manufacturing method has the advantages of being high in efficiency, simple in process, low in raw material price and the like, and can be widely applied to the field of resin-based composite material production and manufacturing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of mold manufacturing, and in particular relates to a low-shrinkage soluble core mold for composite material molding and a manufacturing method thereof. Background Art

[0002] Fiber-reinforced resin-based composite parts are usually manufactured by autoclave process or resin transfer molding (RTM) process, and the shape of the parts needs to be given by the mold. For composite parts with complex inner cavities or hollow composite parts with variable cross-sections, since the inner cavity cannot be obtained by mechanical processing, a core mold is required as a cavity support material, and the core mold is removed after the part is formed. Compared with other mold solutions (such as metal assembly molds, airbags), soluble core molds have outstanding advantages of simple design, convenient use, and easy demolding, which are very suitable for the molding of fiber-reinforced resin-based composite parts. However, the molding process of composite materials usually requires a certain temperature and pressure, and after molding, the surface of the part is not allowed to be processed except for a small amount of grinding. Therefore, the soluble core mold is required not only to have sufficient strength and stiffness to maintain the shape within the use temperature range, but also to have high dimensional accuracy and surface finish. In addition, from the perspective of practical application, the soluble core mold must also have the characteristics of light weight, easy production, low cost, recyclability, and environmental friendliness.

[0003] Traditional soluble core molds are mainly divided into sand cores, gypsum cores and salt cores according to the materials. These core molds have some limitations when used in the manufacture of composite parts: the sand core is heavy and difficult to operate, and the surface quality of the molded parts is not high; the gypsum core itself is brittle and easy to break; the salt core has good comprehensive performance, but the shrinkage rate is extremely high and the precision is difficult to control. Patent CN108864994B provides a soluble core mold using polyvinyl alcohol resin, quartz sand and chopped fibers. Since the polyvinyl alcohol resin used as an adhesive has a high melting point, even if it is modified to reduce the melting point, it still needs to be heated to 170℃~200℃ to melt. Excessive temperature causes the core mold material to shrink significantly during the cooling and shaping process of the mold. Under such conditions, the cost and difficulty of controlling the dimensional accuracy of the core mold increase significantly. Therefore, it is urgent to develop a soluble core mold with low shrinkage, controllable dimensional accuracy and low cost for the manufacture and molding of fiber-reinforced resin-based composite parts. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a low-shrinkage soluble core mold and a manufacturing method thereof for manufacturing fiber-reinforced resin-based composite material parts, which can realize the manufacturing of a soluble core mold with high dimensional accuracy at a relatively low cost and in a simple process.

[0005] The technical solution of the present invention is as follows: the soluble core mold material adopts water-based acrylic resin as an adhesive, and other components are hollow glass microspheres, kaolin, graphite powder and rigid filler. This formula reduces the heating temperature required for the core mold to be shaped to 100°C; the shaping shrinkage rate and mechanical properties of the soluble core mold are regulated by adjusting the proportion of the adhesive water-based acrylic resin, so that the obtained core mold has the lowest shaping shrinkage rate under the premise of having sufficient mechanical properties.

[0006] Hollow glass microspheres can reduce the weight of the core mold, kaolin increases the surface finish of the core mold, and graphite powder increases lubricity and helps to mix the components evenly. Adding these components can make the resulting soluble core mold more in line with the requirements of fiber-reinforced resin-based composite parts manufacturing and molding, but the higher the addition ratio, the lower the rigidity of the resulting core mold, which will cause deformation during use. Therefore, the addition amount of each component must be within a certain mass fraction range to ensure that the core mold has good comprehensive performance and is suitable for use.

[0007] The technical solution of the present invention is as follows:

[0008] A low shrinkage soluble core mold suitable for composite material molding, composed of hollow glass microspheres, kaolin, graphite powder, rigid filler and water-based acrylic resin. Furthermore, the mass fraction of the rigid filler is 50% to 60%, the mass fraction of kaolin is 10% to 15%, the mass fraction of the hollow glass microspheres is 5% to 10%, the mass fraction of the graphite powder is 1% to 5%, and the mass fraction of the water-based acrylic resin is 25% to 30%. Among them, the rigid filler is preferably alumina powder. Furthermore, in addition to alumina powder, the optional rigid filler also includes one or more mixtures of quartz sand, mica powder, gypsum powder, etc. The selected hollow glass microspheres have a particle size range of 20μm to 70μm, and the selected kaolin, graphite powder, and alumina powder have a particle size of 200 mesh.

[0009] Step 1: Alumina powder, kaolin and graphite powder may absorb moisture and agglomerate due to extrusion during storage, so they need to be sieved with a 200-mesh screen before manufacturing.

[0010] Step 2: Weigh kaolin, alumina powder, hollow glass microspheres, and graphite powder respectively, pour them into a container in sequence, and stir at a speed of 100 r / min to 500 r / min for 1 min to 3 min until the four materials are evenly mixed.

[0011] Step 3: Add water-based acrylic resin to the mixed powder, stir at a speed of 200 r / min to 300 r / min for 5 min to 10 min to obtain a uniformly mixed masterbatch.

[0012] Step 4: Clean and degrease the surface of the steel mold, and apply a release agent. Load the evenly mixed masterbatch into the mold, fill and tamp it in 2 or 3 times, and use a tool to scrape off the excess masterbatch on the surface. Then put the mold into the oven, set the temperature to 100℃ for 2 hours, and the heating rate is 1℃ / min~2℃ / min. After the insulation is completed, cool it to room temperature with the furnace and open the mold to obtain a soluble core mold. The burrs and floating sand on the surface of the core mold are removed by grinding with 100-400 mesh sandpaper. According to the needs of use, a gel coat can be sprayed on the surface of the core mold to improve the finish and wear resistance.

[0013] Step 5: After use, the core mold can be dissolved and disintegrated by water, ethanol, or acetone to achieve part demoulding.

[0014] Furthermore, during the oven curing and shaping process described in step 4, the set temperature value can be in the range of 100°C to 110°C.

[0015] Furthermore, during the oven curing and shaping process described in step 4, when the maximum thickness of the core mold is less than 50 mm, the total insulation time is 2 h to 6 h; when the maximum thickness of the core mold is greater than or equal to 50 mm and less than 100 mm, the total insulation time is 6 h to 10 h; when the maximum thickness of the core mold is greater than or equal to 100 mm, the total insulation time is 10 h to 15 h.

[0016] Furthermore, during the oven curing and shaping process described in step 4, in order to ensure that the heat can evenly penetrate into the core mold and avoid the situation where the internal volatiles cannot be discharged due to too fast surface hardening, the process of step 4 can be carried out in a gradient heating and insulation manner. The preferred temperature gradient is: in the first stage, the temperature is raised to 80℃~90℃, and the temperature is kept for 1h~3h; in the second stage, the temperature is raised to 100℃, and the temperature is kept for 2h~4h; further, a third stage can be added, the temperature is raised to 110℃, and the temperature is kept for 2h~8h. The principle of temperature gradient setting is that the larger the size of the core mold, the finer the temperature gradient, and the longer the insulation platform time.

[0017] Beneficial effects of the present invention:

[0018] The present invention aims at the deficiencies of the prior art and provides a low-shrinkage soluble core mold and a method for manufacturing the same. The soluble core mold is suitable for the manufacturing and molding of fiber-reinforced resin-based composite parts, especially for the autoclave process and the RTM process. The core mold material of the present invention has a shrinkage range of 0.2% to 0.6% after solidification and shaping. The soluble core mold manufactured by the method of the present invention is light in weight and has a density of 1.03g / cm 3 ~1.05g / cm 3, only slightly heavier than water. The compression strength can reach more than 10MPa, which can meet the pressure requirements in composite molding. When demolding, the core mold can be dissolved and collapsed by common solvents such as water, ethanol, acetone, etc., and the use cost is low. The manufacturing method involved in the present invention has the advantages of high efficiency, simple process, low raw material price, etc., and can be widely used in the field of resin-based composite material production and manufacturing. DETAILED DESCRIPTION Specific embodiment 1:

[0020] The hollow glass microspheres selected in this embodiment have a particle size distribution D50 value of 40μm and a D90 value of 65μm. Alumina powder is selected as a rigid filler. The mass fraction of alumina powder is 55.5%, the mass fraction of kaolin is 11.5%, the mass fraction of hollow glass microspheres is 5.5%, the mass fraction of graphite powder is 2.5%, and the mass fraction of water-based acrylic resin is 25%. After sieving the alumina powder and kaolin with a 200-mesh sieve, weigh kaolin, alumina powder, hollow glass microspheres, and graphite powder in proportion and put them into a mixer, stir at a speed of 500r / min for 1min to mix evenly. Then add water-based acrylic resin and stir at a speed of 200r / min for 5min. The mixed masterbatch is loaded into the mold, heated to 100°C in an oven at a heating rate of 2°C / min and kept warm for 2h. After the insulation is completed, the mold is opened after cooling to room temperature with the furnace to obtain a soluble core mold. The core mold solidification setting shrinkage rate is 0.21%. After sampling and testing, the bending strength of the core mold material is 2.56MPa, the compression strength is 6.25MPa, and the density is 1.05g / cm 3 The time required for a 100g core mold sample to completely disintegrate in water is 68min. The soluble core mold can be used in the RTM molding process of fiber-reinforced resin-based composite materials. Specific embodiment 2:

[0022] The hollow glass microspheres selected in this embodiment have a particle size distribution D50 value of 40μm and a D90 value of 60μm. Alumina powder is selected as a rigid filler. The mass fraction of alumina powder is 54%, the mass fraction of kaolin is 11%, the mass fraction of hollow glass microspheres is 5.3%, the mass fraction of graphite powder is 2.7%, and the mass fraction of water-based acrylic resin is 27%. After sieving the alumina powder and kaolin with a 200-mesh sieve, weigh the kaolin, alumina powder, hollow glass microspheres, and graphite powder in proportion and put them into a mixer, and stir them at a speed of 200r / min for 3min to mix them evenly. Then add water-based acrylic resin and stir at a speed of 300r / min for 10min. The mixed masterbatch is loaded into the mold, heated to 110°C in an oven at a heating rate of 1°C / min and kept warm for 2h. After the insulation is completed, the mold is opened after cooling to room temperature with the furnace to obtain a soluble core mold. The core mold solidification setting shrinkage rate is 0.53%. After sampling and testing, the bending strength of the core mold material is 10.1MPa, the compressive strength is 10.9MPa, and the density is 1.05g / cm 3 The time required for a 100g core mold sample to completely collapse in water is 87min. The soluble core mold can be used in the autoclave molding process of fiber-reinforced resin-based composite materials.

Claims

1. A low shrinkage soluble core mold suitable for composite material molding, characterized in that: It includes hollow glass microspheres, kaolin, graphite powder, rigid filler and water-based acrylic resin; the mass fraction of the rigid filler is 50% to 60%, the mass fraction of kaolin is 10% to 15%, the mass fraction of the hollow glass microspheres is 5% to 10%, the mass fraction of the graphite powder is 1% to 5%, and the mass fraction of the water-based acrylic resin is 25% to 30%; among which, the rigid filler is alumina powder; the particle size range of the hollow glass microspheres is 20μm to 70μm.

2. A low shrinkage soluble core mold suitable for composite material molding as claimed in claim 1, characterized in that: The rigid filler also includes one or more mixtures of quartz sand, mica powder and gypsum powder.

3. A low shrinkage soluble core mold suitable for composite material molding as claimed in claim 1 or 2, characterized in that: The particle size of the kaolin, graphite powder and alumina powder is 200 meshes.

4. A method for preparing a low shrinkage soluble core mold suitable for composite material molding according to any one of claims 1 to 3, characterized in that: Here are the steps: Step 1: sieve alumina powder, kaolin and graphite powder through a 200-mesh sieve; Step 2: Weigh kaolin, alumina powder, hollow glass microspheres, and graphite powder respectively, pour them into a container in sequence, and stir at a speed of 100 r / min to 500 r / min for 1 min to 3 min until the four materials are evenly mixed; Step 3: Add water-based acrylic resin to the mixed powder, stir at a speed of 200 r / min to 300 r / min for 5 min to 10 min to obtain a uniformly mixed masterbatch; Step 4: Clean and degrease the surface of the steel mold, and apply a release agent; load the evenly mixed masterbatch into the mold, fill and tamp it in 2 or 3 times, and use a tool to scrape off the excess masterbatch on the surface; then put the mold into the oven, set the temperature to 100℃ for 2h, and the heating rate is 1℃ / min~2℃ / min; after the insulation is completed, cool it to room temperature with the furnace and open the mold to obtain a soluble core mold; remove the burrs and floating sand on the surface of the core mold with 100~400 mesh sandpaper; Step 5: After use, the core mold can be dissolved and disintegrated by water, ethanol, or acetone to achieve part demoulding.

5. According to the method for preparing a low-shrinkage soluble core mold suitable for composite material molding as described in claim 4, during the oven curing and shaping process in step 4, the set temperature value is in the range of 100°C to 110°C.

6. According to the method for preparing a low-shrinkage soluble core mold suitable for composite material molding as described in claim 4, during the oven curing and shaping process in step 4, when the maximum thickness of the core mold is less than 50 mm, the total insulation time is 2 h to 6 h; when the maximum thickness of the core mold is greater than or equal to 50 mm and less than 100 mm, the total insulation time is 6 h to 10 h; when the maximum thickness of the core mold is greater than or equal to 100 mm, the total insulation time is 10 h to 15 h.

7. According to the method for preparing a low-shrinkage soluble core mold suitable for composite material molding as described in claim 4, during the oven curing and shaping process in step 4, the process of step 4 can be carried out in a gradient heating and heat preservation manner; the principle of setting the temperature gradient is that the larger the size of the core mold, the finer the temperature gradient, and the longer the time of the heat preservation platform.

8. According to the method for preparing a low-shrinkage soluble core mold suitable for composite material molding as described in claim 7, the temperature gradient is: in the first stage, the temperature is raised to 80°C to 90°C and kept warm for 1h to 3h; in the second stage, the temperature is raised to 100°C and kept warm for 2h to 4h; further, a third stage can be added, the temperature is raised to 110°C and kept warm for 2h to 8h.

Citation Information

Patent Citations

  • A soluble adhesive, a soluble mandrel, and a method for preparing them.

    CN108864994B

  • Waterborne binder and preparation method thereof, and lithium ion battery using waterborne binder

    CN108649226A

  • Water-soluble core mold material for replacing complex core-pulling structure and preparation method of water-soluble core mold material

    CN116442442A

  • Water-soluble organic binder for casting

    CN1175486A

  • Moulding or core sand bonded by biodegradable polymeric binder

    EP2564951A1